Cohesion strategies and genre in expository prose a comparison between the writing of sixth-grade children of ethno-linguistic cultural groups and their literacy materials - Abadiano, Helen Regalado (UMI, 1993)
"This research study focuses on that aspect of classroom literacy practice called "writing" in as much as learning to write in a specific kind of way is part and parcel of children's literacy learning expectations, and the ability to write has become a significant criterion in judging one's "success" or "failure" in literacy learning. More specifically, it addresses "writing" by ethnolinguistic cultural groups and investigates the written cohesion patterns found in their expository writing. It also looks into the written cohesion patterns found in the expository writing of their mainstream counterparts and the expository prose of sixth grade text books which are often the "models" of the genre. Comparisons and contrasts are made between these children's expository writing and the samples of expository writing from their text books. The research study involves a total of 24 sixth grade children from two ethnolinguistic cultural groups--urban African Americans and urban Appalachians, as well as their mainstream culture selected from two sixth grade classes in a Middle School in a large midwesten urban school system. It also includes 96 expository writing samples (four written products per participant) as well as four samples of expository articles from sixth grade commercially produced reading materials in social studies and science text books; and a documentation of classroom literacy practices involving both the teacher and students particularly during children's expository prewriting, writing, and postwriting activities. The data analysis uses Halliday and Hasan's (1976) cohesion analysis which includes identifying the type of cohesive relations -- reference, substitution + ellipses, and lexical cohesion ; examining density of cohesive ties ; and computing of the Cohesion Index. Results suggest that ethnicity, gender, and language variation do not play a major influence in the writing of children in the upper grades. Results also suggest the importance of children's classroom literacy experiences, particularly those that relate to their later writing activities, for them to be able to write "appropriate" texts. This is evident in the similarities found in the children's use of all the major types of cohesive devices and the rank order in the frequency of occurrence of each cohesive devices in their expository writing; also in the sample expository articles taken from the children's text books which suggest the influence "models" of writing may have on children. Thus, the quality and kinds of "models" of writing introduced to children may be crucial to developing their skills in writing." -- abstract